2004
DOI: 10.1038/sj.npp.1300599
|View full text |Cite
|
Sign up to set email alerts
|

Human Cocaine-Seeking Behavior and its Control by Drug-Associated Stimuli in the Laboratory

Abstract: Second-order schedules of drug self-administration were developed to incorporate the effects of drug-related environmental stimuli into an animal model of drug abuse, making it more similar to human situations. Ironically, little is known about how human subjects behave under these schedules. In this study, human volunteers with a history of cocaine use worked on a second-order schedule in which every 100th lever response produced an auditory-visual brief stimulus (2 s). The first stimulus produced after 1 h w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…In rodents and primates, second-order schedules of reinforcement provide a well established method of investigating the neurobiology of drug seeking that is under the control of drug-associated CSs (Goldberg et al, 1975;Everitt and Robbins, 2000;Schindler et al, 2002). Indeed, cocaine seeking under a second-order schedule of reinforcement in humans shares many similarities to that observed in rats and monkeys (Panlilio et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rodents and primates, second-order schedules of reinforcement provide a well established method of investigating the neurobiology of drug seeking that is under the control of drug-associated CSs (Goldberg et al, 1975;Everitt and Robbins, 2000;Schindler et al, 2002). Indeed, cocaine seeking under a second-order schedule of reinforcement in humans shares many similarities to that observed in rats and monkeys (Panlilio et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Drug-paired conditioned stimuli (CSs) can, as conditioned reinforcers, maintain drug seeking and precipitate drug craving and relapse (Stewart et al, 1984;Ehrman et al, 1992;Carter and Tiffany, 1999;Everitt and Robbins, 2000;Schindler et al, 2002;Panlilio et al, 2005). In rodents and primates, second-order schedules of reinforcement provide a well established method of investigating the neurobiology of drug seeking that is under the control of drug-associated CSs (Goldberg et al, 1975;Everitt and Robbins, 2000;Schindler et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical studies, second-order schedules of reinforcement have been shown to support robust and persistent operant responding for both natural and drug reinforcers (Alderson, Robbins, & Everitt, 2000;Goldberg, Kelleher, & Goldberg, 1981;Goldberg & Tang, 1977;Katz, 1979Katz, , 1980Mello et al, 1995). In addition, laboratory studies suggest that humans will learn to respond to a variety of reinforcers under second-order schedules (Lamb et al, 1991;Mello, Mendelson, Palmieri, Lex, & Teoh, 1990;Panlilio et al, 2005).In applying an operant schedule that has reliably been demonstrated to produce robust and prolonged responding with relatively low-cost prizes, the procedure used here may have important clinical benefits, reinforcing abstinence in a cost-effective manner. Our patients in the high-density contingent group received prizes worth on average only $286 during the 12-week intervention, less than the cost of commonly studied voucher-based CM procedures (Downey, Helmus, & Schuster, 2000;Higgins, Badger, & Budney, 2000;Piotrowski et al, 1999;Robles et al, 2000;Silverman et al, 1996).…”
mentioning
confidence: 99%
“…The invigorating impact of drug-associated conditioned stimuli (CSs) on seeking behavior has been operationalized in models of CS-induced relapse (Ciccocioppo et al, 2002;Gipson et al, 2013;Lee et al, 2006;Marchant et al, 2013) as well as cue-controlled cocaineor heroin-seeking behavior (Arroyo et al, 1998;Economidou et al, 2011;Giuliano et al, 2013) and CS-dependent seeking of high incentive foods that is associated with obesity and binge eating (Giuliano et al, 2012). Although outbred rat strains will respond instrumentally for alcohol (Augier et al, 2014), and alcohol-associated CSs can elicit approach (Tomie and Sharma, 2014) and serve as conditioned reinforcers (Smith et al, 1977;Panlilio et al, 2004;Milton et al, 2012;Rodd et al, 2004), attempts to establish vigorous CS-dependent alcohol seeking that mediates delays to the opportunity to drink have proven difficult, probably because alcohol is an apparently weak reinforcer for rats with little or no propensity to drink.…”
Section: Introductionmentioning
confidence: 99%